Delivering multidisciplinary neuromuscular care for children via telehealth. Issue 1 (29th April 2022) - Carroll, Kate; Adams, Justine; de Valle, Katy; Forbes, Robin; Kennedy, Rachel A.; Kornberg, Andrew J.; Vandeleur, Moya; Villano, Daniella; Woodcock, Ian R.; Yiu, Eppie M.; Ryan, Monique M.; Davidson, Zoe
Abstract: Introduction/Aims: In response to coronavirus disease 2019 (COVID‐19) pandemic restrictions int 2020, our face‐to‐face (F2F) multidisciplinary neuromuscular clinic (NMC) transitioned to widespread use of telehealth (TH). This study aimed to (1) understand parent/guardian, child, and clinician perceptions of TH; (2) examine TH‐related changes in clinical activity; and (3) use these findings to inform a future model of care for the NMC. Methods: A clinical audit was undertaken to examine clinical activity throughout 2018–2020. Online surveys were distributed to clinicians and parents of children attending the NMC via TH in 2020. A working group of clinicians created a checklist to guide a future hybrid model of TH and F2F care. Results: Total clinical activity in 2020 was maintained from previous years; 62.8% of all appointments occurred via TH, and 82.3% of patients attended NMC by TH at least once. Ninety‐nine parents (30.6% response rate), 52 children, and 17 clinicians (77% response rate) responded to the survey. All groups reported better interaction when F2F compared to TH. Eighty percent of parents identified advantages of TH and reported lower levels of stress. A lack of "hands‐on" physical assessment was identified by parents and clinicians as a TH limitation. Most families (68.1% of parents; 58.8% of children) and all clinicians indicated a preference for a mix of TH and F2F NMC appointments in the future. Discussion: This study has informed a checklist to guide future TH use in a new hybrid model of care. Further investigation is required to assess health impacts of TH use in pediatric neuromuscular care. Abstract :